Developing critical thinking skills assessment for pre-service elementary school teacher about the basic concept of science: validity and reliability. (June 2020) - Patonah, S; Rahardjo, S B; Cari,; Sajidan,
Abstract: One of learning outcomes in higher education is the ability to apply logical, innovative, and critical thinking in the science and technology learning. But the instruments to measure it are still few, so this study was aimed to develop critical thinking skills instruments for elementary school pre-service teachers. The mixed-method was used in this research. It consisted of 3 stages, namely, 1) the initial study, 2) design and review, and 3) try out. 122 students were selected as samples. The instrument consisted of 20 items about the Basic Science Concept Development. The items developed according to the indicators of critical thinking skills by Facione. The results showed that all items have a fit in the range of 0.77 - 1.20; mean INFIT MNSQ of 0.99, SD of 0.11; and internal consistency of 0.58. Overall, all items were declared valid and reliable.